Digital Wallet and Mobile Banking Adoption Among Rural Bank Customer - Parakh, Santosh Dilipkumar; Ukhalkar, Prakash; Sanu, Leena (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
This study provides a rural perspective to the global research and literature on rural customer for the adoption of Digital Wallet and Mobile banking. It empirically examines the most influencing factors that stimulates digital wallet and mobile banking user for service adoption. A sample of 300 customers was surveyed from the rural areas of Maharashtra state, INDIA. A Simple Random Sampling method is used for selections of area from Maharashtra state and Chi-square testing was used in stated hypothesis. An influence of qualitative factors were identified by Factor Analysis with the help of K-M-O test of Sphericity. The study therefore concludes that Security-Privacy, Trust and Familiarity has significant impact on Mobile banking adoption. And qualitative factors such has Prestige, Speed, Trust, Safety & Security, Easiness and Familiarity has major influence on rural customer for the adopting of Digital Wallet and Mobile banking services offered from financial institution.Keywords: Digital Wallet, Mobile Banking, Rural Customer, Adoption Factors.* Vidya Pratishthan’s Institute of Information Technology (VIIT), Baramati, Maharashtra 413133, India** Pimpri Chinchwad College of Engineering, Pune, Maharashtra, Sector -26, Pradhikaran, Nigdi,Near Akurdi Railway Station, Pune - 411 044, India*** Christ College, Pune, Maharashtra, 26/4 A, Off Pune Nagar Road, Opposite Weikfield IT Citi Info Park, Wadgaon Sheri, Pune, Maharashtra 411014, India https://doi.org/10.21632/irjbs.13.3.215-226